2001
DOI: 10.1006/dbio.2000.9992
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Signaling in the Absence of Furin Processing of Notch1

Abstract: Notch is a conserved cell surface receptor that is activated through direct contact with neighboring ligand-expressing cells. The primary 300-kDa translation product of the Notch1 gene (p300) is cleaved by a furin-like convertase to generate a heterodimeric, cell-surface receptor composed of 180- (p180) and 120- (p120) kDa polypeptides. Heterodimeric Notch is thought to be the only form of the receptor which is both present on the cell surface and able to generate an intracellular signal in response to ligand.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 24 publications
6
80
0
Order By: Relevance
“…These findings raise questions about the specificity of these inhibitors in the complex cell-signaling system. Furthermore, ␥-secretase inhibitors do not differentiate between the Notch ligands involved in regulation of T cell functions, and a previous report showed that Notch signaling could be induced independently of ␥-secretase in mutant forms of Notch (43) suggesting that the ␥-secretase inhibitor may block only a part of Notch's functions. Significant genetic evidence of the existence of CSL-independent Notch signaling has been shown although the molecular components of this pathway and its downstream targets remain largely unknown (44).…”
Section: Discussionmentioning
confidence: 97%
“…These findings raise questions about the specificity of these inhibitors in the complex cell-signaling system. Furthermore, ␥-secretase inhibitors do not differentiate between the Notch ligands involved in regulation of T cell functions, and a previous report showed that Notch signaling could be induced independently of ␥-secretase in mutant forms of Notch (43) suggesting that the ␥-secretase inhibitor may block only a part of Notch's functions. Significant genetic evidence of the existence of CSL-independent Notch signaling has been shown although the molecular components of this pathway and its downstream targets remain largely unknown (44).…”
Section: Discussionmentioning
confidence: 97%
“…By blocking the proteolytic release of N-IC, these compounds block the classical CSL-dependent Notch signaling pathway. Importantly, however, mutant forms of Notch which are resistant to furin cleavage in the secretory pathway, and therefore are resistant to subsequent ␥ secretase cleavage, are still able to inhibit myogenesis in a ligand-dependent but CSL-independent manner (30). This demonstrates the existence of signaling events that are cleavage ϩ T cell cytokine responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Surface Biotinylation-Isolation of cell surface proteins was performed essentially as previously described with minor modifications (20). Briefly, naive or differentiated PC12 cells were rinsed 3 times with ice-cold PBS and then incubated with either PBS alone (non-biotinylated controls) or PBS containing 0.5 mg/ml Sulfo-NHS-LC-Biotin (Pierce) for 2 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%